Long Term Athlete Development British Diving - Foley, S.; White, K.; Bellan, J.; Warr, C.; Smith, K. (sportcentric, 2005)
Diving is very much an anaerobic and explosive sport and therefore very different to swimming. It has very different needs and requirements. It is fair to say that the swimming pool water is about the only thing they have in common. Even the swimwear is now different! The ages for competing are also very much younger for diving, similar to gymnastics. Thus requiring a lot of attention to child growth and Development. After years of writing plans for World Class Performance, Potential and Start it`s great that the sport of diving can now link these with Club Development to create a Long Term Athlete Development (LTAD) model specifically for diving. Club Development is the key to long term success as only a hand full of clubs are able to deliver all stages of the LTAD. British Diving have now established a clear pathway for divers from Learn to Dive, right through to winning Olympic medals. Training regimes, explaining what a diver should be doing, how much and how often will assist divers and coaches to reach their full potential and in turn help to achieve British Diving`s long term goals. Alongside the LTAD sits a new Coach Education Programme that links with every stage of the framework. This is a first for British Diving and in fact, throughout most of the world. What a fantastic opportunity for clubs and coaches to apply LTAD principles and know exactly what they need to do to go to the next level.